Business of love: exploring motivations to use and sentiments towards online dating using big data analytics - Elshazly, Ahmed Elsaid Abdelhalim Eliwa (2018)
Online Dating has increased in popularity over the past few years. With the evolution of technology and the internet’s increasing capabilities of interaction, online dating has altered the dating world and offered a convenient, fast, and trendy way to find a partner. In fact, it has yielded an industry that has been growing at a quick pace of 5.3% yearly and was estimated to reach $3 billion of revenues in the US only in 2016, generated by hundreds of online dating businesses. However, both big and small players in the multi-billion dollar industry compete to bring in as many subscribers as they can, using various state-of the-art technologies which are the key to their success. To stay ahead of the competition, in-depth knowledge of consumers is an irreplaceable factor. Adopting the “Uses and Gratifications” approach, the aim of this paper is to boost the knowledge of businesses operating in the field by shedding light on the primary motivations of online daters. It also examines the user experience by identifying sentiments toward dating platforms and finds more insights regarding the causes behind those sentiments. A large set of reviews publicly posted by users was employed as the source of data. The study carried out on 1346 reviews about 47 dating platforms has revealed six primary motivations for using online dating. People surf dating sites to seek love or a serious relationship, meet new people, engage in casual relationships, utilize the convenience offered through virtual dating, follow the trend of meeting others via dating sites, or to validate their personal image which in return provides self-satisfaction to the dater. Among all, the first motivation appeared to be the strongest. The employed text analytics tools named SAS VA and Microsoft Power BI have shown positive, average, and negative sentiments across users towards online dating businesses. Of these, the larger group of users expressed negative sentiment. The study demonstrated that the negative experience was mainly attributed to gaps in the offered services, technology, and quality of other subscribers.